Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/nl500485n
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Single Layer Graphene Oxide Reduction through Spatially Resolved, Single Sheet Absorption/Emission Microscopy

Abstract: Laser reduction of graphene oxide (GO) offers unique opportunities for the rapid, nonchemical production of graphene. By tuning relevant reduction parameters, the band gap and conductivity of reduced GO can be precisely controlled. In situ monitoring of single layer GO reduction is therefore essential. In this report, we show the direct observation of laser-induced, single layer GO reduction through correlated changes to its absorption and emission. Absorption/emission movies illustrate the initial stages of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 39 publications
(104 reference statements)
1
60
1
1
Order By: Relevance
“…As an illustration, the last two panels in Fig. 2.2b show that GO's absorption dramatically increases across the visible upon the removal of these functionalities and approaches graphene's 2.3 %A limit [21,26].…”
Section: Optical Properties Of Graphene Go and Rgomentioning
confidence: 98%
See 3 more Smart Citations
“…As an illustration, the last two panels in Fig. 2.2b show that GO's absorption dramatically increases across the visible upon the removal of these functionalities and approaches graphene's 2.3 %A limit [21,26].…”
Section: Optical Properties Of Graphene Go and Rgomentioning
confidence: 98%
“…By contrast, GO's optical absorption is nearly an order of magnitude smaller (~0.3 %A, second panel, Fig. 2.2b) [21,22]. Furthermore, GO's absorption spectrum is wavelength dependent; it peaks in the UV/blue edge of the visible spectrum and falls towards the near infrared (NIR).…”
Section: Optical Properties Of Graphene Go and Rgomentioning
confidence: 99%
See 2 more Smart Citations
“…While this is difficult to achieve in threedimensional (3D) crystalline materials, the 2D carbon lattice found in graphene is ideal for mechanochemistry since it is atomically flat, can be produced with exceptional crystalline quality, can be functionalized with a wide range of chemical groups and is easily characterized by conventional surface science techniques 13,14 . Chemically modifying graphene markedly alters its optical 15 , electronic 16 and lubricating 17,18 properties. It should be noted that while prior work has shown that scanning probes can remove functional groups by locally applying heat 16,19 or electronic potential 20 ; mechanochemical cleavage by a scanning probe has not been addressed.…”
mentioning
confidence: 99%